2008
DOI: 10.1017/s0960258508082986
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-harvest influences on physiological dormancy alleviation of an AustralianAsteraceaespecies:Actinobole uliginosum(A. Gray) H. Eichler

Abstract: 2008). Pre-and post-harvest inuences on physiological dormancy alleviation of an Australian Asteraceae species: Actinobole uliginosum (A. Gray) H. AbstractThe effects of maternal air temperature and soil moisture upon seed physiological dormancy (PD) alleviation of an Australian native Asteraceae were investigated. From the onset of flowering, Actinobole uliginosum plants growing ex situ were subjected to either a warm (mean 268C) or cool (mean 178C) temperature regime, with adequate or limited water availabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…These results were relatively insensitive to water reduction treatments for both species, indicating that temperature, rather than moisture stress, is the most influential component of the maternal environment on primary dormancy (Hoyle et al. , c). Our results for the five native species were consistent with this maternal temperature effect, although we were unable to account for genetic differences between the maternal populations of each species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were relatively insensitive to water reduction treatments for both species, indicating that temperature, rather than moisture stress, is the most influential component of the maternal environment on primary dormancy (Hoyle et al. , c). Our results for the five native species were consistent with this maternal temperature effect, although we were unable to account for genetic differences between the maternal populations of each species.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental work on two Australian PD species, Actinobole uliginosum (Asteraceae, common in YGJW) and Goodenia fascicularis (Goodeniaceae), revealed that warmer maternal environments accelerate the reproductive period and reduce the levels of primary dormancy in freshly dispersed seeds (Hoyle et al. , c). These results were relatively insensitive to water reduction treatments for both species, indicating that temperature, rather than moisture stress, is the most influential component of the maternal environment on primary dormancy (Hoyle et al.…”
Section: Discussionmentioning
confidence: 99%
“…data). Seeds of all focal species were collected from the study site in 2010 and underwent a 2-week dry-after-ripening treatment at 40°C to alleviate dormancy (Hoyle, Daws, Steadman, & Adkins, 2008). Seeds were placed on sterilised germination paper in culture plates exposed to one of three constant temperature: 7°C, 14°C and 25°C.…”
Section: Germination Ratesmentioning
confidence: 99%
“…Prior to germination, seeds were placed at 35 ∘ C overnight since annual plants from semiarid climates often require dry hot conditions to break dormancy [25]. Twenty seeds of each species were used in three replicates per treatment.…”
Section: Ex Situ Seed Germinationmentioning
confidence: 99%